FACTORS AFFECTING ENTREPRENEURIAL PERFORMANCE OF INFORMAL SECTOR ENTERPRISES IN BATURAJA - Harby R Wiralaga (STIE DWI SAKTI BATURAJA, 2019)
AbstractThe research objective is to examine factors affecting entrepreneurial performance of informal sector enterprises in Baturaja. The research applied area sampling, a method of sampling used when no complete frame of reference is available. Cross sectional primary data is collected by observation and structured interview. The data was analyzed by MLR model by using SPSS; as to meet requirement of MLR model, the normality, multicollinearity and heteroscedasticity tests are performed. The model confirms that the observed change in entrepreneurial performance attributed to the identified factors are 28,50% while the remaining 71,50% could be explained by other factors. Results from analysis of variance where F (8; 71) = 4,934; P < 0,001; R2 = 0,357; adjusted R2= 0,285; proved that the model is fit to explain and to yield t test results. In other words, the overall regression model was highly significant.The MLR analysis reveals that startup capital does significantly affect entrepreneurial performance of informal sector enterprises (P = 0,001; P < 0,05); working capital does significantly affect the entrepreneurial performance of informal sector enterprises (P= 0,003; P < 0,05); and labor employment does significantly affect entrepreneurial performance of informal sector enterprises in Baturaja (P= 0,032; P < 0.05). On the contrary, academic degree, vending location, operating hour, gender, and business establishment age are not found to have significant affect on entrepreneurial performance of informal sector enterprises in Baturaja.